Respostas

  • Usuário do Brainly
2013-05-28T15:05:08-03:00

a) 52-4\text{x}=0

 

4\text{x}=52

 

\text{x}=\dfrac{52}{4}=13

 

 

b) (\text{x}-2)^2-9=0

 

\text{x}^2-4\text{x}+4-9=0

 

\text{x}^2-4\text{x}-5=0

 

\text{x}=\dfrac{-(-4)\pm\sqrt{(-4)^2-4\cdot1\cdot(-5)}}{2\cdot1}=\dfrac{4\pm6}{2}

 

\text{x}_1=\dfrac{4+6}{2}=5

 

\text{x}_2=\dfrac{4-6}{2}=-1

2013-05-28T15:12:58-03:00

- 4x = - 52    . (-1)

4x = 52

x = 52 / 4

x = 13 

 

 

x² + 2 . x . - 2 + 2² - 9 = 0

x² - 4x + 4 - 9 = 0

x² - 4x - 5 =  0

s = 4

P = -5 ( -1 , 5 )

 

x¹= -1

x²= 5